The role of objectification in young men's perpetration of intimate partner violence. - Adriana Vargas Sáenz; Nick Haslam (PLoS ONE)
Theorists have argued that objectification is implicated in men's violence against women. Growing correlational and experimental evidence supports this claim. However, little research has studied the link between objectification and violence perpetrated by intimate partners. Three studies examined this link in relation to several forms of violent behavior. Study 1 (N = 215) found that men who implicitly associated women with objects were more likely to perpetrate sexual and physical violence against their female romantic partner, independent of their levels of hostile sexism. Study 2 (N = 325) replicated this finding but examined automatic associations with men's intimate partners rather than women as a class. Greater implicit objectification was again associated with self-reported physical violence and with a behavioral proxy measure of aggression among participants who responded most strongly to an experimental provocation. Study 3 (N = 192) manipulated objectification by inducing a physical appearance-focus mindset and found that the manipulation increased men's tendency to respond violently toward their partner. By implication, objectification appears to play a significant role in facilitating men's violence in romantic relationships.